Non-targeted Plasma Metabolome of Early and Late Lactation Gilts - Rempel, Lea A.; Miles, Jeremy R.; Oliver, William T.; Broeckling, Corey D. (Frontiers in Molecular Biosciences, 2016)
Female pigs nursing their first litter (first-parity gilts) have increased energy requirements not only to support their piglets, but they themselves are still maturing. Non-targeted plasma metabolomics were used to investigate the differences between (1) post-farrowing and weaning (early or late lactation), (2) degree of body condition loss after lactation (extreme or minimal), and (3) interactions; to potentially identify compounds or pathways that could aide in alleviating energetic demands of lactation in gilts. Twenty first-parity gilts were selected with similar (P ≥ 0.4475) number of piglets born and nursed, and similar (P ≥ 0.3141) body condition traits (e.g., body weight and backfat thickness) post-farrowing, yet exhibited minimal or extreme loss (P ≤ 0.0094) in body weight (8.6 ± 1.48 kg and 26.1 ± 1.90 kg, respectively) and backfat thickness (1.3 ± 0.67 mm and 4.7 ± 0.86 mm, respectively) following lactation (weaning). Plasma samples from first-parity gilts at post-farrowing and weaning were investigated using UPLC-MS and GC-MS to generate a comprehensive metabolic profile. Each approach yielded approximately 700 detected features. An ANOVA was performed on each detected compound in R for time of collection, body condition change, and the interaction, followed by a false discovery correction. Two unknown features were different (P ≤ 0.05) for extreme vs. minimal body condition change. Several compound differences (P ≤ 0.05) were identified between post-farrowing and weaning. Thirty-two features detected by UPLC-MS had at least a log2 fold-change of ±1.0 while only 18 features had a log2 fold-change of ±0.6 or more for the significant GC-MS features. Annotation implicated various metabolic pathways. Creatinine was greater at weaning (P = 0.0224) and others have reported increased serum concentrations of creatinine in response to body weight loss. Hippurate and caprolactam, associated with protein catabolism, were also greater (P ≤ 0.0166) at weaning. Phospholipid features (P ≤ 0.0347) and inositol-related features (P ≤ 0.0236) were also greater at weaning. Inositol features may exert insulin-like effects. The energetic demands of lactation in gilts nursing their first litter indicated a greater difference exists between early and late lactation regardless of body condition loss.